Value, knowledge and implementation on evidence‐based practice among nurse managers in china: A regional cross‐sectional survey. (22nd January 2020) - Chen, Liling; Wu, Yanni; Zhou, Chunlan; Li, Xiaoxia; Zhao, Huihui
Abstract: Aim: To describe the value, knowledge and implementation of evidenced‐based practice (EBP) among Chinese nurse managers and explore its influencing factors. Background: Although much of literature have reported the importance of nurse managers in pushing EBP progress and encouraged them to engage in EBP activities, the extent to which nurse managers engage in EBP is unclear. Methods: A cross‐sectional web‐based survey was applied to 1, 166 nurse managers recruited from 54 hospitals in Guangdong Province, China. Descriptive statistics, t ‐tests or one‐way ANOVAs, Spearman's correlation and multiple regression analysis were used to analyse the data. Results: The average scores of the Quick‐EBP‐VIK were with the mean of 2.62 (±0.56). Result showed that educational background, professional title, whether they have received EBP education or training, and EBP organisational culture and readiness are the factors influencing managers' total Quick‐EBP‐VIK score, with 43.5% of the variance explained by these factors. Conclusions: Nurse managers had positive attitudes towards EBP, but they lacked the EBP knowledge and rarely implemented EBP. Furthermore, supportive organisational environment, effective education and training can help to enhance EBP knowledge and skills of managers. Implications of nursing management: The competence of nurse managers for EBP implementation should be taken seriously. Personal and organisational strategies which can strengthen managers' EBP knowledge and skills need to be developed and conducted.